Laboratory investigation of GCL moisture absorption from leachate-contaminated subsoil - Hamed Ghanbari; Mohammad Reza Boroomand; Hamid Reza Saba (رویکردهای نوین در مهندسی آب و محیط زیست)
Before contact with leachate, GCL must be sufficiently hydrated, or in other words absorb moisture, so that it has sealing properties and prevents the penetration of leachate into the subsoil. GCL absorbs moisture from the subsoil and swells and gets sealing properties, therefore, investigating the moisture absorption behavior of GCL from the subsoil has become important and has become the subject of research by some researchers. The purpose of this research is to investigate the moisture absorption behavior of GCL from the subsoil contaminated with leachate and what effect the presence of leachate has on the hydration of GCL and its sealing properties. In this research, the moisture absorption behavior of GCL from three types of sandy soil, mixed and fine-grained, for each of these soils in three different initial moisture percentages, for sandy soil including 8%, 13%, and 23%, for mixed soil and Fine-grained soil including 2.4%, 12.4% and 17.4% was investigated and its results were presented, then the moisture absorption behavior of GCL in the presence of leachate was investigated for all three types of soil in the condition that the soils were in three types of leachate percentage. Various were contaminated. The results of investigating the moisture absorption behavior of GCL show that in the presence of leachate, the amount of moisture absorbed by GCL in the tested time period is less than the expected value and the presence of leachate has a significant negative effect on GCL hydration by more than 2 to 6 times.